Based on science a systematic review of study methodologies investigating performance in 15 s Rugby women student-athletes: the impact of sex - Rishiraj, N.; Prasad, N.; Blair, M.; Timmins, B. (Sport Sciences for Health, 2025)
Purpose Researchers have suggested that most sports science data have been derived from studies with men as participants, reducing the application of these data to women athletes due to physiological differences between the sexes. This systematic review aimed to evaluate, using science, the influence of sex on study methodologies investigating physiological performance in 15 s Rugby (RU) female student-athletes. Furthermore, we summarise the importance of physiological differences between the sexes required for each topic of applied sports medicine and sports science in RU women student-athletes.